Natural properties of confined masonry buildings - experimental case studies and possible inferences. (3rd June 2019) - Nema, Harshit; Basu, Dhiman
Construction of faculty housing and student-s hostels in a fully-residential 400-acre academic campus of Indian Institute of Technology Gandhinagar (IITGN) in the State of Gujarat, India is the first large scale confined masonry construction in the country. Knowledge of dynamic properties of these buildings will provide valuable inputs to the seismic design recommendations of confined masonry buildings. Ambient and forced vibration tests (AVT and FVT) are conducted in some of the constructed buildings for the natural period and damping ratio. This paper presents the details of such case studies and compares the experimental results with general expectation considering reinforced concrete buildings with in filled masonry wall as the basis. Also recommended in this paper are some of the fines tunings in the experimental framework of conducting AVT and FVT, and processing the recorded data to identify the natural frequency with greater confidence level.